Emergency cerclage following a standardized protocol offers an effective and safe therapeutic option for women with high risk for prematurity – a retrospective monocentric cohort study on 130 pregnancies and 155 neonates. (17th December 2021) - Schneider, Katja; Fimmers, Rolf; Jörgens, Matthias; Peter, Susanne; Pelzer, Volker; Redlich, Tim
Abstract: Objective: To present emergency cerclage (EC) as a safe and effective therapeutic option for prevention of prematurity in women with advanced cervical dilation in second-trimester pregnancy. It is focused on seemingly futile situations like cervical dilation >5 cm, bulging membranes and multifetal pregnancies. The outcomes of interest are the prolongation of pregnancy, gestational age at delivery and neonatal morbidity and mortality related to distinct risk factors. Study design: Retrospective monocentric cohort study involving 130 pregnancies (105 single and 25 twin pregnancies) and 155 neonates by using a standardized protocol. Women between 18 and 28 gestational weeks with cervical shortening of <10 mm + cervical dilation >2 cm and/or bulging membranes were included. Analyses of maternal and neonatal parameters were done by chart review. Results: The medium gestational age at delivery was 35 5/7 week with a medium interval from cerclage placement to delivery of 83 days. Overall, 46.5% (72/155) neonates were born beyond 37 weeks, extreme prematurity of less than 28 gestational weeks was observed in 14.8% (23/155), no miscarriage before 22 weeks was documented. The neonatal mortality was 1.9% (3/155). Neonatal deaths and morbidity was related to severe prematurity exclusively. The association of amnion-infection syndromes and failing therapy was significantly with respect to bulging membranes and advanced cervical dilation >5 cm. Conclusions: Even in futile cases EC can be an option to save the pregnancy and prevent severe prematurity. However, a standardized protocol is imminent for successful therapy and every indication has to be a case by case decision.